The effect of training to the development of bottling industry: A case of Coca-Cola Kwanza Limited - Augustine, Scolastika (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial /fulfilment of the requirements for the award Degree of Master of Science in Human Resource Management (Msc-HRM) of Mzumbe University.